A Study on Fandom and Fan Culture: Socioeconomic Implications in the Digital Era - Jasmine Syifa Hermawan; Margaret Ginting (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2024)
The study of fandom and fan culture has grown in significance in the digital age. Fandoms are communities of individuals with shared interests who participate in activities like reading, viewing, and making fan art. Fandom's socioeconomic effects include its contribution to the production and consumption of cultural content as well as its effects on the travel, entertainment, and retail industries. But there are also societal effects like